Dynamics of the Philippine market sectors a DDC analysis - Gordo, Gilbert M.; Bautista, Carlos C. (Quezon City Cesar E.A. Virata School of Business, University of the Philippines Diliman, 2015)
Aims to describe market sector volatility behavior in the Philippines. Examines the behavior market sector indices (financials, industrial, holding firms, property, services and mining &oil) using dynamic conditional correlation (DCC) analysis, a multivariate GARCGH model. Also shows how the DCC is used for firm level data.
Thesis (Doctor of Philosophy in Business Administration)--University of the Philippines Diliman
Keywords: Investment analysis; Investments -- Mathematical models; Portfolio analysis